Negative regulator NLRC3: Its potential role and regulatory mechanism in immune response and immune-related diseases - Sun, Deyi; Xu, Jiqian; Zhang, Wanying; Song, Chaoying; Gao, Chenggang; He, Yajun; Shang, You (Frontiers in Immunology, 2022)
NLRC3 is a member of the pattern recognition receptors nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs) family, and plays a pivotal regulatory role in modulating the activation of immune cells. In macrophages, NLRC3 inhibits the activation of the NF-κB signaling pathway, the STING/TBK1 signaling pathway, and the formation of the inflammasome. In the context of T cells immune response, NLRC3 prevents the activation of T cells by regulating the function of dendritic cells and directly influencing the function of T cells. Different from other pattern recognition receptors, NLRC3 is more closely associated with regulatory activity than pathogens recognition, it influences the fates of cells, for example, prevents proliferation, promotes apoptosis and inhibits pyroptosis. These cellular functions regulated by NLRC3 are involved in the development processes of a variety of diseases, such as infectious disease, sterile inflammatory diseases, and cancer. However, its characteristics, function and regulatory mechanism in immune response and immune-related diseases have not been addressed fully. In this review, we elaborate the potential roles of NLRC3 from several different levels, include molecular mechanism, cellular functions in the immune-related diseases.